IMPLEMENTASI KEBIJAKAN ANTI DUMPING CINA TERHADAP PRODUK BROILER ASAL AMERIKA SERIKAT (TAHUN 2010) - Dandy Nakito; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In February 2010, China announced placed tarrif on broiler chicken product from the United States. China claims that U.S has been unfairly flooding the China markets with cheap broiler chicken product, so that impact to China jobs and China unions. Many criticized the tariffs as a protectionist move by the China, because in recent years, the United States placed tariffs on one China infant industry with same reason. The focus of this research is to analyze the real motif China placed tariff on broiler chicken product from U.S. Are this have any reason connected to U.S placed tarif on China infant industry. This research uses Politic Economy Theory related to International Trade theory which has been revealed by Heckscher-Ohlin This research is Qualitative research which is used by library observation.The result of this research prove that there’sno relevant reason owned China to impose of anti-dumping and countervailing duties on U.S broiler chicken product. In four meeting in the WTO DSB Panel, declared victory for the U.S, as well as announced that all the Chine data and evidence is a mistaken.Keywords: Anti-Dumping, Broiler Chicken, Countervailing Duties.